2018
DOI: 10.1145/3272127.3275047
|View full text |Cite
|
Sign up to set email alerts
|

P aparazzi

Abstract: The image processing pipeline boasts a wide variety of complex filters and effects. Translating an individual effect to operate on 3D surface geometry inevitably results in a bespoke algorithm. Instead, we propose a general-purpose back-end optimization that allows users to edit an input 3D surface by simply selecting an off-the-shelf image processing filter. We achieve this by constructing a differentiable triangle mesh renderer, with which we can back propagate changes in the image do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Neural mesh renderer (NMR) [KUH18] approximates the backward gradient for the rasterization operation using a handcrafted function for visibility changes. [LTJ18] proposed Paparazzi, an analytic differentiable renderer for mesh geometry processing using image filters. Petersen et al [PBDCO19] presented Pix2Vex , a C ∞ differentiable renderer via soft blending schemes of nearby triangles, and [LLCL19] introduced Soft Rasterizer , which renders and aggregates the probabilistic maps of mesh triangles, allowing gradient flow from the rendered pixels to the occluded and far‐range vertices.…”
Section: Fundamentals Of Neural Renderingmentioning
confidence: 99%
“…Neural mesh renderer (NMR) [KUH18] approximates the backward gradient for the rasterization operation using a handcrafted function for visibility changes. [LTJ18] proposed Paparazzi, an analytic differentiable renderer for mesh geometry processing using image filters. Petersen et al [PBDCO19] presented Pix2Vex , a C ∞ differentiable renderer via soft blending schemes of nearby triangles, and [LLCL19] introduced Soft Rasterizer , which renders and aggregates the probabilistic maps of mesh triangles, allowing gradient flow from the rendered pixels to the occluded and far‐range vertices.…”
Section: Fundamentals Of Neural Renderingmentioning
confidence: 99%
“…the parameters can be processed. Mesh‐based differentiable renderers [ 26 , 27 , 28 , 29 ] have been proposed to optimize various scene parameters such as geometry, illumination, textures, or materials.…”
Section: Related Workmentioning
confidence: 99%
“…With the advent of techniques adopting neural fields to reconstruct 3D representations [25][26][27][28][29], Neural Radiance Field (NeRF) [1] proposed by Mildenhall et al showed a promising result without the requirement of exact 3D geometry of each object in the scene. Compared to previous approaches which require a pre-defined representation of the scene by meshes [30,31], voxels [25,26], or point clouds [27,32], NeRF only requires a set of densely captured 2D images and corresponding camera parameters of each image. Despite its light requirements, it demonstrates quality reconstruction of the complex geometry of scenes.…”
Section: Related Workmentioning
confidence: 99%